IMPLEMENTATION OF FREE LEARNING POLICY-INDEPENDENT CAMPUS PROGRAMS ON MASTERING COURSE THEORY OF FOUNDATION DESIGN - Artiwi, Nila Prasetyo; Rosdiyani, Telly (Universitas Ibn Khaldun Bogor, 2021)
Minister of Education and Culture Regulation No. 3 of 2020, entitles students to 3 semesters of study outside their study program. Through the Free Learning Policy - Independent Campus program, students have wide opportunity to be able to choose the learning method and place they want which is believed to be able to enrich and increase their insight and competence in the real world according to their passion and aspirations. The